(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
As the world is emerging towards new trends and technologies; there is a need to invent something that is more attractive and useful for the citizens. This research work highlights a very young area of application and provides a comprehensive overview of the application of robotics in the food industry. In this new technological age, all jobs depend on a technology called automation. New research works are developed in the market instead of human workers being the fashion and new passion today. In this context, we develop the concept of the food serving robots (FSR) in this work. It required Arduino board and the Arduino IDE to build. In this research work the board is predefined by using color sensors and the obstacle sensor to identify the tables. This Application can be used in any hotel and restaurant, regular cycles. The use of robots in the food management system is very trendy. Internet of Things mechanisms (IoTM) are widely used to avoid human manual work. It also reduces the number of employees in a workplace. Once the structure is created, it works according to the user’s instructions. Here in this Application we will create this robot for food delivery in hotels. In this paper, we consider two tables to show the operation of the robo and the so-called food delivery robot. In this robo build it required components like Arduino board, gear motor, motor controller, IR obstacle sensor, battery (6 volt), and jumper wires.